Strengthening and Management of The Campus-Based Indonesian Language Institution for Foreign Speakers (BIPA) at The PBSI Study Program of UMN Al Washliyah With The Language Center of North Sumatra Province - Hasibuan, Abdullah; Nirmawan, Nirmawan; Zulfitri, Zulfitri (West Science Interdisciplinary Studies, 2025)
The Indonesian language has experienced very rapid development in various parts of the world. This is also influenced by various factors, including Indonesia's state relations with other countries in various sectors, including economic, political, social, and cultural. Through these relations, the important role of the Indonesian language is believed to be a potential element related to the position of the Indonesian language in the international arena. In addition, in accordance with the mandate of Law Number 24 of 2009 concerning the Flag, Language, and National Emblem, namely making the Indonesian language an international language, various diplomatic methods are carried out gradually and systematically under the Ministry of Education and Culture. One of the linguistic diplomacy missions intensively carried out by the Indonesian government is to facilitate the Indonesian language teaching program for Foreign Speakers (BIPA) to many countries that already have bilateral and multilateral cooperation with Indonesia. Through language, a person can communicate with others, even though they have different cultural backgrounds. Likewise, with Indonesian language being studied by people who are not native speakers of the language. Therefore, the BIPA teaching program, which is one of the advantages of this diplomatic mission, continues to be intensified in various universities, agencies, or language institutions abroad.